Penerapan metode bernyanyi untuk meningkatkan minat belajar siswa di TK Negeri Pembina Lebong - Joko Prayudha.S; Malik, Azis Abdul (SISTEMA: Jurnal Pendidikan, 2021)
Attracting students' interest in learning is one of the things that is difficult for teachers to do. Therefore, the teacher must be able to make the learning atmosphere as attractive as possible so that students do not feel bored during learning. This study aims to investigate the implementation of the singing method while studying in order to be able to provide enthusiasm for learning or interest in learning to students at TK Negeri Pembina Lebong. This type of research is qualitative research using a descriptive approach. The subjects in this study were all students in the TK Negeri Pembina with a total of 38 students and three teachers who taught. Data were collected by used observations during learning and interviews with teachers who taught. The results obtained indicate that by using the singing method students feel more enthusiastic in learning and are able to increase students' self-confidence attitudes. Keywords: Singing Method, Learning Interest